Technological and Islamic environments: Selection from Literature Review Resources - Yusuf Durachman; Adrian Sean Bein; Eka Purnama Harahap; Tarisya Ramadhan; Fitra Putri Oganda (International Institute for Advanced Science & Technology (IIAST), 2021)
This article is displayed in two fundamental segments drawing consideration to investigate standards, beginning with tawḥīd as a result it was a vision conveyed of the overall troubles of mankind with other animals within the world. At that point continue with a survey of the two standards, specifically the caliph, the caliph of people on soil, and the guideline of trust (amānah). The moment portion examines illustrations of infringement of these principles in three fundamental ranges: the spread of debasement (fasād) within the world, extraction and squander (isrāf) and enduring (ḍarar). The most objective of the talk in this area is the administration of people, or maybe the fumble of the world and its assets so that mankind itself gets to be the most noteworthy casualty of its own disappointments. The conclusion draws consideration to how comprehensive Islamic sees and lessons can make chosen commitments to the wrangle about possible worldwide climate change. This article concludes with suggestions for conceivable changes.